МОДЕЛЬ ДИАГНОСТИКИ КАЧЕСТВА ОБУЧЕНИЯ В ПЕДАГОГИЧЕСКОМ ИНСТИТУТЕ И В УНИВЕРСИТЕТЕ - Каипова, С.К.; Далиева, П. (SCIENCE and SOCIETY, 2025)
The article examines and presents a structural and methodological model for organizing diagnostics in a higner education establishment.